Cyril Tourneur : déictique et/ou didascalie, écriture d’un décor virtuel - Danièle Berton-Charrière (Revue LISA)
In Cyril Tourneur’s Laugh and Lie Down or The World’s Folly and The Transformed Metamorphosis the scene is set in enclosed claustrophobic spaces, frightening replicas of hell and purgatory in which shadows occupy the whole locus. The camera-obscura-like microcosms, respectively given as ‘the world’s folly’ and a ‘concavitie’, can be seen as specific theatrical places devoted to entertainment and revelling, including fantasmagory. It was then fashionable to stage the spectacular in garden grottoes and follies. The evolution of mechanical devices amplified the performances in which the audience took an active part. The pamphlet and poem by Tourneur render the ‘texts in contexts’ relationship as if particular images of the period were cast and traced on their sheets through the magnifying glass of a politically involved and committed author. Deictic and Didascalia punctuate the virtual and/or real journey, onstage, offstage and backstage.